Sinergi Hukum dan Pengelolaan Keuangan dalam Mendorong Akuntabilitas Dana Desa di Kabupaten Karawang: Synergy Between Law and Financial Management in Promoting Accountability for Village Funds in Karawang Regency - Tinambunan, Wahyu Donri; Triyunarti, Wiwin; Okabrian, Soni; Nurhanifah, Afifa (Jurnal Dedikasi Hukum, 2025)
The management of village funds is a crucial aspect in community development and empowerment at the village level. However, implementation in the field still faces various challenges, such as weak legal capacity of village officials, lack of financial accountability, and lack of community participation in supervision. This condition has the potential to cause budget irregularities and hinder village development goals. Therefore, an integrated effort is needed that combines legal and accounting knowledge to encourage transparent, accountable, and participatory governance of village funds. This service activity aims to increase the capacity of village and community apparatus through an interdisciplinary approach. From the legal side, participants will be given an understanding of village financial management regulations, the legal responsibilities of village officials, and criminal risks in budget abuse. In terms of accounting, the training will focus on recording transactions, preparing financial statements, and simulating simple audits that are relevant to village practices. This activity uses a participatory method with the Participatory Action Research (PAR) model, which involves village officials and the community actively in each stage of the activity. This approach was chosen so that the results of the service were really in accordance with the needs of the field and could be applied directly by the participants. The implementation of activities is carried out through an interdisciplinary approach, which is a combination of the fields of law and accounting. The targeted outputs of this activity include: (1) increasing legal and accounting literacy among village officials; (2) the preparation of practical modules for the management of village funds based on law and accounting; and (3) the formation of an accountability-aware village community that can be a driver of budget supervision based on citizen participation. Abstrak Pengelolaan dana desa merupakan aspek krusial dalam pembangunan dan pemberdayaan masyarakat di tingkat desa. Namun, implementasi di lapangan masih menghadapi berbagai tantangan, seperti lemahnya kapasitas hukum perangkat desa, minimnya akuntabilitas keuangan, serta kurangnya partisipasi masyarakat dalam pengawasan. Kondisi ini berpotensi menimbulkan penyimpangan anggaran dan menghambat tujuan pembangunan desa. Oleh karena itu, perlu upaya terpadu yang menggabungkan keilmuan hukum dan akuntansi untuk mendorong tata kelola dana desa yang transparan, akuntabel, dan partisipatif. Kegiatan pengabdian ini bertujuan untuk meningkatkan kapasitas perangkat desa dan masyarakat melalui pendekatan interdisipliner. Dari sisi hukum, peserta akan diberikan pemahaman terkait regulasi pengelolaan keuangan desa, tanggung jawab hukum aparatur desa, serta risiko pidana dalam penyalahgunaan anggaran. Dari sisi akuntansi, pelatihan akan difokuskan pada pencatatan transaksi, penyusunan laporan keuangan, serta simulasi audit sederhana yang relevan dengan praktik desa. Kegiatan ini menggunakan metode partisipatif dengan model Participatory Action Research (PAR), yaitu melibatkan perangkat desa dan masyarakat secara aktif dalam setiap tahap kegiatan. Pendekatan ini dipilih agar hasil pengabdian benar-benar sesuai dengan kebutuhan lapangan dan dapat diterapkan langsung oleh peserta. Pelaksanaan kegiatan dilakukan melalui pendekatan interdisipliner, yaitu gabungan antara bidang hukum dan akuntansi. Luaran yang ditargetkan dari kegiatan ini meliputi: (1) peningkatan literasi hukum dan akuntansi di kalangan perangkat desa; (2) tersusunnya modul praktis pengelolaan dana desa berbasis hukum dan akuntansi; dan (3) terbentuknya komunitas desa sadar akuntabilitas yang dapat menjadi penggerak pengawasan anggaran berbasis partisipasi warga.